Assessing the Satisfaction of Women Members of Cooperative Societies - Gopika B; Jisha K K; K Gireesan; S Nehru (Journal of Extension Education)
In Kerala, a constituent state of India, the expansion of agricultural and related cooperatives indicates the general degree of contentment among its members. This study aims to analyse data from a primary survey among agricultural and milk cooperatives to elucidate the elements contributing to members’ satisfaction. Descriptive statistics indicate that most female members of the cooperatives have completed only a basic level of education, and furthermore, only a minority of them occupy important roles within these organizations. The estimated structural equation model depicts the dynamics of satisfaction in detail. According to the study, members’ participation in cooperative activities yields a variety of benefits, thereby increasing their overall satisfaction.